Patient and Provider Perspectives on Mammographic Breast Density Notification Legislation. Issue 1 (November 2016) - Klinger, Elissa V.; Kaplan, Celia P.; St. Hubert, Stella; Birdwell, Robyn L.; Haas, Jennifer S.
Background: Patient advocacy has fostered the implementation of mammographic breast density (MBD) notification legislation in many states. Little is known about the perspectives of women, primary care physicians (PCPs), and breast radiologists in response to this legislation. The objective of this research was to elicit qualitative information from these multiple stakeholders to understand varied perspectives on the subject of MBD notification and inform best practices around implementation.Methods: Content analysis of narrative data from focus groups with women (2 groups, total of 16 participants) and in-depth interviews with PCPs (n = 7) and breast radiologists (n = 7).Results: Three major themes emerged from the data: 1) knowledge and general attitudes about legislation, 2) concerns about consequences, and 3) actions patients and clinicians should consider based on MBD information. For each of these themes, the views of women, PCPs, and radiologists often demonstrated different perspectives.Conclusion: This work supports the need for clear and concise tools for patients and providers to understand MBD in the context of a woman's overall breast cancer risk with guidance on next steps.